Estimation of cell cycle duration and standardization of cytogenetic protocol Guadua angustifolia Kunth var. angustifolia (Bambusoideae, Poaceae). (Revista de Investigaciones Universidad del Quindío, 2012)
Guadua angustifolia has economic and ecological importance both in its native and in those where it has been introduced which is why they have developed multiple research aimed to determine the genetic diver-sity and its physical and mechanical properties, among others, which programs are aimed at conservation, propagation and breeding. The present study evaluated the cell cycle and cytogenetic technique was stan-dardized from root meristem. Mitotic time was determined by performing collection of apices each hour for 24 hours. Furthermore, techniques were applied: Also, pre-treatment, fixation, hydrolysis, staining and mounting techniques were implemented in order to accumulate metaphase cells to achieve the standardiza-tion of the protocol for cytogenetic studies. The results indicated that this species has a short cell cycle in meristematic tissue which does not exceed five hours and a bimodal behavior in their mitotic activity. The standardization of the protocol for obtaining metaphase cells was achieved by pretreatment with colchicine 1% fixation for 24 hours with Carnoy, double hydrolysis with 2N HCl and a cocktail enzyme cellulase and pectinase macerozyme, staining with acetic orcein or DAPI, as the case and tissue assembly through the techniques of squash or extension.
Keywords: Guadua angustifolia; Cell Cycle; plant Cytogenetic; meristematic root